Bioelectrical impedance vector analysis and body composition in cervical spinal cord injury: A pilot study - Bauermann, Andreia; Costa e Silva, Anselmo de Athayde; Figueiredo, Flávia; Koury, Josely Correa (Frontiers in Nutrition, 2022)
Introduction: Body composition assessment in cervical spinal cord injury (c-SCI) individuals is important to monitor the fat free-mass (FFM) loss, due to immobilization, or gain, due to exercise practice. Single frequency bioelectrical impedance analysis (SF-BIA) is low in cost, simple and easy. Objectives: The aims of this study are: to evaluate the concordance between the FFM values obtained using dual X-ray absorptiometry (DXA) and the three SF-BIA previous predictive equations; and to test the applicability of the bioelectrical impedance vector analysis (BIVA). Methods: Twenty-three c-SCI males were divided into two groups: physically active (PA; n=13; at least 150 minutes/week) and non-active individuals (NPA) and were assessed by DXA and SF-BIA simultaneously. Results: FFM values were similar between groups PA and NPA. Considering all participants, FFM values obtained by Kocina-Heyward (>11%) and Sun (<15.4%) predictive equations were different when compared to DXA (p<0.01). However, Buchholz's et al predictive equation showed FFM values similar to DXA, but presented poor concordance (<7%, p=0.99; concordance coefficient=0.85). BIVA showed consistency in ellipse distribution using FFM obtained using Buchholz et al predictive equation. Conclusions: The use of nonspecific BIA equations can lead to misinterpretation in FFM values in male c-SCI individuals. Predictive equations for this group need to be developed.